2014
DOI: 10.3389/fphys.2014.00289
|View full text |Cite
|
Sign up to set email alerts
|

Functional insights into modulation of BKCa channel activity to alter myometrial contractility

Abstract: The large-conductance voltage- and Ca2+-activated K+ channel (BKCa) is an important regulator of membrane excitability in a wide variety of cells and tissues. In myometrial smooth muscle, activation of BKCa plays essential roles in buffering contractility to maintain uterine quiescence during pregnancy and in the transition to a more contractile state at the onset of labor. Multiple mechanisms of modulation have been described to alter BKCa channel activity, expression, and cellular localization. In the myomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 170 publications
(226 reference statements)
0
31
0
Order By: Relevance
“…Thereafter the field was open for more modulatory factors from signaling pathways, such as by G-proteins or second messengers, by redox mechanisms, by the action of gasotransmitters, such as nitric oxide (NO), carbon monoxide (CO), or hydrogen sulfide (H 2 S) [ 1 , 44 , 57 , 59 , 86 , 150 ] or more recently by S-acylation (the post-translational attachment of fatty acids to cysteine residues) [ 151 ]. Modulation of ion channels is involved in physiological processes such as transmitter release, hormone secretion or muscle contraction to name just a few [ 11 , 52 , 152 , 153 , 154 , 155 ]. Alterations of channels proteins by oxidative stress and its functional consequences constitutes one further way of channel modulation in a great variety of cells and tissues which will be covered in the following sections.…”
Section: Ion Channels and Oxidative Stressmentioning
confidence: 99%
“…Thereafter the field was open for more modulatory factors from signaling pathways, such as by G-proteins or second messengers, by redox mechanisms, by the action of gasotransmitters, such as nitric oxide (NO), carbon monoxide (CO), or hydrogen sulfide (H 2 S) [ 1 , 44 , 57 , 59 , 86 , 150 ] or more recently by S-acylation (the post-translational attachment of fatty acids to cysteine residues) [ 151 ]. Modulation of ion channels is involved in physiological processes such as transmitter release, hormone secretion or muscle contraction to name just a few [ 11 , 52 , 152 , 153 , 154 , 155 ]. Alterations of channels proteins by oxidative stress and its functional consequences constitutes one further way of channel modulation in a great variety of cells and tissues which will be covered in the following sections.…”
Section: Ion Channels and Oxidative Stressmentioning
confidence: 99%
“…BKCa was studied in uterus smooth muscle and was reported that BKCa is over expressed in adenomyosis tissues, and it might cause abnormal muscle contractility that induces the inflammation effects, endometrium impairment and pain [ 13 ]. Moreover, the expression of BKCa in pregnant myometrium is reduced during labor and related with onset of parturition [ 14 , 15 ]. Recently, Li et al [ 16 ] reported the role of BKCa in endometrial cancer HEC-1-B cells.…”
Section: Introductionmentioning
confidence: 99%
“…The BK Ca channel is made up of four pore-forming ␣-subunits to which accessory ␤-subunits can attach (51,63). Four classes of ␤-subunits have been identified, although there may be more (62,84). These accessory ␤-subunits can regulate voltage and Ca 2ϩ sensitivity to specialize BK Ca channel-opening behavior, with the ␤ 1 -subunit being the most common ␤-subunit in vascular smooth muscle cells (13,63).…”
Section: Prenatal Chronic Hypoxia and Enos-dependent Relaxationmentioning
confidence: 99%